Prevention, Medical Management, and Adjudication of Workplace Injuries: A Thirty-Two Year Follow-up of an Integrated Workers' Compensation Program. Issue 10 (21st October 2021) - Bernacki, Edward J.; Kalia, Nimisha; Soistman, Sharon; Minor, Sebastian A.; Barry, Jill; Lavin, Robert A.; Tao, Xuguang (Grant)
Abstract : Objective: To describe the cost outcomes of an integrated workers' compensation program. Methods: We studied a population that increased from 20K to 59K, incurring 8807 lost-time claims between 1988 and 2020. Results: Lost-time claims decreased from 22.15 to 4.32 per 1000 employees (1988 to 2020), and total closed lost-time claim costs per 100 payroll, decreased from 0.62 to 0.17 (1988 to 2017). The percent of claims resolved within 3 years of the accident increased from 10% to 89% (1988 to 2017). Adjusting for medical inflation and wage increases, total workers' compensation benefits paid per claim decreased 124 per year, medical benefits decreased 45 per year and indemnity benefits decreased 79 per year. Conclusion: On both a population (per employee) and on a per claim basis, workers' compensation costs decreased substantially, which is attributable to improvements in accident prevention and decreases in claim duration.